New species and new records of Syndicus Motschulsky (Coleoptera, Staphylinidae, Scydmaeninae) PAWEŁ JAŁOSZYŃSKI (Poland) - Jałoszyński, Paweł (Zootaxa, 2011)
Three new species of Syndicus Motschulsky, 1851 are described: S. (s. str.) phangngaensis sp. n. (Thailand: Phang Nga), S. (s. str.) kampucheanus sp. n. (Cambodia: Mondol Kiri), and S. (Semisyndicus) schuelkei sp. n. (China: Yunnan). New distributional records are presented for S. paeninsularis bilobatus Jałoszyński, 2004 (from Laos: Bolikhamsai and Cambodia: Mondol Kiri), S. (s. str.) echinatus Jałoszyński, 2004 (from W Malaysia: Selangor), S. (s. str.) difficilis Jałoszyński, 2004 (from Thailand: Chiang Mai), S. (s. str.) himalayanus Franz, 1975 (from Nepal: Chitwan), and S. (Semisyndicus) leai leai Franz, 1971 (from W Malaysia: Selangor). The female of S. paeninsularis bilobatus is described for the first time; this species and S. kampucheanus are the first Scydmaeninae reported to occur in Cambodia.